Cytotoxicity profile of highly hydrogenated graphene - Chng, Elaine Lay Khim (2014)
Graphene and its graphene-related counterparts have been considered the future of advanced nanomaterials owing to their exemplary properties. An increase in their potential applications in the biomedical field has led to serious concerns regarding their safety and impact on health. To understand the toxicity profile for a particular type of graphene utilized in a given application, it is important to recognize the differences between the graphene-related components and correlate their cellular toxicity effects to the attributed physiochemical properties. In this study, the cytoxicity effects of highly hydrogenated graphene (HHG) and its graphene oxide (GO) counterpart on the basis of in vitro toxicological assessments are reported and the effects correlated with the physiochemical properties of the tested nanomaterials. Upon 24 h exposure to the nanomaterials, a dose-dependent cellular cytotoxic effect was exhibited and the HHG was observed to be more cytotoxic than its GO control. Detailed characterization revealed an extensive C[BOND]H sp3 network on the carbon backbone of HHG with few oxygen-containing groups, as opposed to the presence of large amounts of oxygen-containing groups on the GO. It is therefore hypothesized that the preferential adsorption of micronutrients on the surface of the HHG nanomaterial by means of hydrophobic interactions resulted in a reduction in the bioavailability of nutrients required for cellular viability. The nanotoxicological profile of highly hydrogenated graphene is assessed for the first time in our study, thereby paving the way for further evaluation of the toxicity risks involved with the utilization of various graphene-related nanomaterials in the real world.